Promising Antidepressant Potential: The Role of Lactobacillus rhamnosus GG in Mental Health and Stress Response - Isik, Musab; Kose, Fadime; Ozbayer, Cansu; Budak, Ozcan; Kaya, Rumeysa Keles; Erdogan, Derya Guzel; Demirci, Mehmet Arif (Springer, 2025)
Chronic stress is linked to changes in brain physiology and functioning, affects the central nervous system (CNS), and causes psychiatric diseases such as depression and anxiety. In this study, antidepressant effects of the probiotic bacterium Lactobacillus rhamnosus GG (ATCC 53103) (LGG) (15 x 10(8) cfu/ml/day) on the mechanisms playing a role in the pathophysiology of depression were investigated, and the results were compared with the effects of bupropion (20 mg/kg/day) and venlafaxine (20 mg/kg/day). A total of 56 male Wistar Albino rats were used in control, stress, bupropion, venlafaxine, LGG, bupropion + stress, venlafaxine + stress, LGG + stress groups, n = 7 each. Changes in the body weight of the rats during the experiment were determined by weight measurement. Gene expression levels were determined by the RT-PCR method. Four different behavioral tests were performed to evaluate depressive behaviors (sucrose preference test, three-chamber sociability test (social interaction test), elevated plus maze test, forced swim test). LGG treatment was effective in reducing depressive-like behaviors, increased BDNF level, 5-HT1A, DRD1, ADRA-2A, GABA-A alpha 1, CNR1 expression levels in the hippocampus and NOD1 receptor expression level in the small intestine (p < 0.05), and also decreased neurodegeneration level, glial cell activity, and intestinal permeability in depressed rats. As a result, it was revealed in this study for the first time that the LGG probiotic bacterium has antidepressant properties and was found to be more effective than the antidepressant drugs bupropion and venlafaxine. Our results suggest that LGG is a potential psychobiotic bacterium and can be useful to treat depression. It may be an effective and useful option in combating depression.
Keywords: Depression-Like Behavior; Chronic Mild Stress; Forced Swim Test; Gaba-A Receptor; Protein-Kinase Phosphatase-1; Messenger-Rna Expression; Cannabinoid Cb1 Receptor; Neurotrophic Factor Bdnf; Autistic-Like Behaviors; Early-Life Stress